The internationalization of small and medium enterprises in regional and global value chains - Hank Lim; Fukunari Kimura (Asian Development Bank Institute (ADBI), 2010)
Production networks and the regional division of labor have been established in East Asia resulting in massive vertical intra-industry trade in parts and components within the region. This phenomenon is known as cross-border production sharing or the fragmentation of production processes into many stages across different countries. New development strategies claim that participation in international production and distribution networks is the key to accelerating economic development in the era of globalization. This process suggests that vertical input-output linkages between local firms and multinational corporations are the most powerful channels to accelerate technology transfers and spillovers. Given the trends of globalization and economic integration in East Asia, there is significant potential for the small and medium enterprise (SME) sector to increase its contribution to the region's development through greater participation in global value chains. However, multiple market failures exist with regard to the development of SMEs and local entrepreneurship. These risks can be mitigated by proper policy measures such as strengthening technological and human resource capabilities through better networking and facilitating access to financing for SMEs. Despite many distortions and inefficiencies in implementing regional economic integration schemes in East Asia, there are many cumulative positive effects contributing to the emerging trend internationalization of SMEs in the region. This process can be significantly strengthened by creating a positive business environment through the standardization of products and services, rules and regulations, and a seamless market infrastructure in the region.
Keywords: D20; 330